دور المعلم الاول كمشرف مقيم في التنمية المهنية للمعلمين في مدارس الحلقة الثانية من التعليم الاساسي بمحاظة مسقط (من وجهه نظر المعلمين) Dawr al-mu'allim al-awwal kamushrif muqimfi al-tanmiyah al-mahdiyah lil-mu'allimin fi madaris al-halqah al-thaniyah min al-ta'lim al-asasi bi-muhafazah masqt (min wajah nazar al-mu'allimin) - Alhadidi, Ibrahim Ali Mubarak; Al-Hidabi, Dawood Abdulmalek Yahya; Mohammed Rawash, Fouad Mahmoud (2019)
This quantitative study aimed to diagnose the role of the first teacher as a supervisor in the professional development of teachers in the second cycle of basic education schools in Muscat Governorate, by revealing the supervisory practices of the first teachers as supervisors in different fields, as well as revealing the differences among the study sample according to variables: gender and experience. The researcher used the descriptive analytical method, designed a questionnaire of (30) statements related to: planning, implementation and field follow-up and evaluation). The study population consisted of (1820) male and female teachers at the second cycle. A random sample of (395) was taken; they are (200) male teachers and (195) females. And to collect data for the study, a in a, systematic way, consisting male and female teachers, with After the quantitative and descriptive analysis in statistical data processing with (SPSS) the findings revealed that; The role of the first teachers in the development came with an average degree in all fields according to teachers point of view. The findings also showed the presence of statistically significant differences at the level of (0.01≥ α) according to (gender) in favor of females, finally there were no statistically differences at the level of (0.05≥ α) according to the experience variable.